The Model of Holistic Development of the Elderly’s Quality of Life through Sustainable Participation Process: A Case Study of Tha Takiab District, Chacheongsao Province, Thailand - Nawasanan Wongprasit (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This participatory action research was conducted with mixed method. The research was done with Plan-Do-Check-Action process. The research objectives were to create a model of the holistic development of the elderly’s quality of life through sustainable participation process in Tha Takiab District, Chachoengsao Province, Thailand. The key informants of this research consisted of elderly, families, government officers, community leaders, and local leaders. Derived from purposive sampling appropriately compatible with the research, 50 key informants were selected through snowball technique. The data collection was done through focus group. The population of quantitative research were 85 elderly living in Moo 2 of Tha Kan Sub-district, Tha Takiab District, Chachoengsao Province. The sample of 70 people was determined with Krejcie & Morgan table at the reliability level of 95%, using simple random sampling. The statistics used for quantitative data analysis was percentage, means, standard deviation, and ANOVA. The content analysis was used with qualitative data. The research results found that the model of promoting holistic quality of life through participation process for sustainability of the elderly or the warm house model (HESS Model) consisted of 4 dimensions as follows:H: Health refers to the dimension of good physical and mental health of the elderly. The elderly must have knowledge of self-care and be able to take care of themselves, as appropriate for each individual’s E: Economic means the elderly who were responsible for their self-reliant. They should work according to their physical condition and spend economically. S: Safety means good surroundings with safety for the elderly, both inside and outside their home, including elderly toilets, travel, roads, various places in the community and fitness centers. S: Social Support means good support from society, such as establishing a network of elderly people in their own communities and develop guidelines in mutual caring for older people.